2011
DOI: 10.1038/asiamat.2011.147
|View full text |Cite
|
Sign up to set email alerts
|

DNA-based switchable devices and materials

Abstract: Studies on DNA molecules have long been focused on its biological functions, since the discovery of the molecular structure of DNA by Watson and Crick [1] in 1953. DNA is known to be composed of adenine (A), guanine (G), cytosine (C) and thymine (T), and the Watson-Crick interaction of A-T and C-G base-pairing leads to the formation of the double-helix structure when sequences are complementary; this base-pairing process is also referred to as hybridization. Single-stranded DNA (ssDNA) is considered flexible,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 72 publications
0
54
0
Order By: Relevance
“…74 In particular, we have observed the evolution of surface-confined DNA probes with rational design from 1D to 2D and then to 3D, which greatly improves our ability to control the density, orientation and passivation of the surface. On the basis of these studies, a variety of electrochemical and optical biosensors have been constructed for the detection of DNA/RNA hybridization, SNP genotyping and microRNA biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…74 In particular, we have observed the evolution of surface-confined DNA probes with rational design from 1D to 2D and then to 3D, which greatly improves our ability to control the density, orientation and passivation of the surface. On the basis of these studies, a variety of electrochemical and optical biosensors have been constructed for the detection of DNA/RNA hybridization, SNP genotyping and microRNA biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…To improve the mechanical properties of chemically crosslinked hydrogels, researchers have developed ingenious strategies, including nanocomposite hydrogels, double-network hydrogels, hybrid crosslinking hydrogels and tetra-polyethylene glycol hydrogels. [14][15][16][17][18][19][20][21][22] Recently, increasing research attention has been dedicated to enhancing the mechanical performance of physically crosslinked supramolecular hydrogels. One recent study demonstrated very tough physical hydrogels composed of polyampholytes.…”
mentioning
confidence: 99%
“…Scientists are currently interested in finding ways to mimic enzyme regulatory circuitry outside of the cell 4,5 , not only to increase our knowledge of cellular metabolism but also so that we may create man-made nanoreactors that have potential utility in applications ranging from diagnostics to the production of high-value chemicals [6][7][8] and smart materials 9 . DNA nanostructures are promising scaffolds for use in the organization of molecules on the nanoscale because they can be engineered to site-specifically incorporate functional elements in precise geometries [10][11][12] and to enable nanomechanical control capabilities 13,14 . Examples of such structures include autonomous walkers 15,16 , nanotweezers [17][18][19][20] and nanocages for controlled encapsulation and payload release 21,22 .…”
mentioning
confidence: 99%